Pairwise-Stability and Nash Equilibria in Network Formation - Antoni Calvó-Armengol; Rahmi Ilkiliç (Fondazione Eni Enrico Mattei (FEEM), 2005)
Suppose that individual payoffs depend on the network connecting them. Consider the following simultaneous move game of network formation: players announce independently the links they wish to form, and links are formed only under mutual consent. We provide necessary and sufficient conditions on the network link marginal payoffs such that the set of pairwise stable, pairwise-Nash and proper equilibrium networks coincide, where pairwise stable networks are robust to one-link deviations, while pairwise-Nash networks are robust to one-link creation but multi-link severance. Under these conditions, proper equilibria in pure strategies are fully characterized by one-link deviation checks.
Keywords: C62; C72; D85; L14; 330; Network formation; Pairwise-stability; Proper equilibrium; Nash-Gleichgewicht; Netzwerk; Spieltheorie